Experimental investigations of noise and vibration characteristics of gasoline-methanol blend fuelled gasoline direct injection engine and their relationship with combustion characteristics. (25th July 2019) - Sharma, Nikhil; Patel, Chetankumar; Tiwari, Nachiketa; Agarwal, Avinash Kumar
Graphical abstract: Highlights: Gasohol exhibited relatively higher P, Pmax, HRR, RoPR and CHR. With increasing engine speed, HRRmax increased. Gasohols showed 1–3 dB(A) higher total noise than gasoline. Gasoline exhibited highest vibrations amongst all test fuels. Total noise was 5–8 dB higher than corresponding combustion noise. Higher load did not necessarily result in increased combustion noise. Abstract: Engine noise and vibrations are influenced by engine's combustion characteristics in addition to contributions from moving components. Combustion characteristics in-turn depend on various parameters such as fuel type, engine load, engine speed, spark timing etc. Low-carbon intensity fuels such as methanol have emerged as an attractive alternative to gasoline because of potential of their production from renewable resources and their higher octane rating. This experimental study was carried out in a single cylinder gasoline direct injection (GDI) research engine to investigate engine's noise, and vibration characteristics and correlate them with the combustion characteristics of the engine. In this study, 10% (v/v) and 20% (v/v) methanol was blended with gasoline (M10 and M20), and these test fuels were evaluated at varying engine loads and speeds vis-à-vis baseline gasoline (G100). It was found that methanol-gasoline blends evaluated in this study generated relatively higher in-cylinder pressure, higher HRR, higher rate of pressure rise (RoPR) and cumulative heat release (CHR) compared to G100, which influenced engine's noise and vibration characteristics significantly.